âMUMI DANSAâ (Merchandise Unik, Menarik dan Edukatif dengan Desain Peta) - Handayani, Tiara; Gustiar, Gin Gin; Lestari, Sri; Silmi, Zidni Farhati; Nuradi, Hanif (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
MUMI DANSA is one of the many alternatives of creative art that is able to give educative introduction about the culture of Nusantara.Â The goal of the project and the products is to have innovative point of view that could be given out into products design, the aim is also to provide fields of jobs, and educative points of view that could give knowledge and introduction about uniqueness of Nusantara. The project is done with 4 methods, which are promotion and publication, marketing, production, and methods for research and design development.Â The MUMI DANSA products which are t-shirts and accessories.Â Keywords : MUMI DANSA, educative, culture of Nusantara, merchandise